EDUCATION MARKETING STRATEGY IN IMPROVING THE IMAGE OF MTS MASYARIQUL ANWAR CARINGIN - Eman Sulaeman; Aap Siti Ulyani; Yuda Rudiana; Abdul Muin Bahaf (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2023)
This study aims to analyze the educational marketing strategies used by MTs Masyariqul Anwar Caringin in improving the image of educational institutions. The image of educational institutions has an important role in attracting prospective students and maintaining the trust of stakeholders, this study was conducted at MTs Masyariqul Anwar Caringin, a madrasah in the Caringin area. The research method used is qualitative method with case study approach. Data was collected through interviews, observations, and analysis of documents related to marketing strategies carried out by the agency. The collected data is then analyzed using descriptive analysis techniques. The results showed that MTs Masyariqul Anwar Caringin has implemented several effective educational marketing strategies. The strategy includes the use of social media to promote the institution, cooperation with external parties in holding joint activities, and the development of excellent programs that attract prospective students. In addition, good communication with parents of students and the surrounding community is also an important factor in improving the image of the institution. However, the study also identified several challenges in implementing educational marketing strategies. Such challenges include limited resources, competition with other educational institutions, and changing trends in student and parent preferences. To overcome these challenges, MTs Masyariqul Anwar Caringin needs to continue to develop responsive and innovative marketing strategies, as well as strengthen collaboration with external parties. This research contributes to the understanding of the importance of educational marketing strategies in improving the image of educational institutions. The implications of this research can be used as a guide for other educational institutions in developing effective marketing strategies to improve their image in society